The Effectiveness of Implementing Project Based Learning with a Scientific Approach in Increasing Understanding of Personal Safety Skills for Children Aged 5-6 Years - Nissa, Nurul A'inun; Rohmah, Naili (BELIA Early Childhood Education Papers, 2025)
This study aims to determine the effectiveness of implementing Project Based Learning with a scientific approach in improving the understanding of Personal Safety Skills in children aged 5-6 years. This study uses a quantitative approach with a One Group Pretest-Posttest Design experimental method by providing treatment to the children. This study involves 25 children from TK Pertiwi 14.13.18 Seliling, selected using total sampling/census technique. The data collection technique used was oral tests and documentation. Statistical analysis used the Paired Sample T-test analysis technique through IBM SPSS Statistic 25 software. The research results from the t-test calculations obtained a significance value of 0.000 < 0.05, so